Spatial regulation of contractility by Neuralized and Bearded during furrow invagination in Drosophila. - Perez-Mockus, G.; Mazouni, K.; Roca, V.; Corradi, G.; Conte, V.; Schweisguth, F. (Nature communications, 2017)
Embryo-scale morphogenesis arises from patterned mechanical forces. During Drosophila gastrulation, actomyosin contractility drives apical constriction in ventral cells, leading to furrow formation and mesoderm invagination. It remains unclear whether and how mechanical properties of the ectoderm influence this process. Here, we show that Neuralized (Neur), an E3 ubiquitin ligase active in the mesoderm, regulates collective apical constriction and furrow formation. Conversely, the Bearded (Brd) proteins antagonize maternal Neur and lower medial-apical contractility in the ectoderm: in Brd-mutant embryos, the ventral furrow invaginates properly but rapidly unfolds as medial MyoII levels increase in the ectoderm. Increasing contractility in the ectoderm via activated Rho similarly triggers furrow unfolding whereas decreasing contractility restores furrow invagination in Brd-mutant embryos. Thus, the inhibition of Neur by Brd in the ectoderm differentiates the mechanics of the ectoderm from that of the mesoderm and patterns the activity of MyoII along the dorsal-ventral axis.